2018
DOI: 10.1111/jocn.14219
|View full text |Cite
|
Sign up to set email alerts
|

Examining the content and moderators of women's fears for giving birth: A meta‐synthesis

Abstract: Identification of the elements and moderators of FOC provide an insight into the potential mechanisms that contribute to women's fears, which can be used to inform methods of identifying women with FOC or a basis upon which to base supportive strategies to reduce women's fears for giving birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 59 publications
5
45
0
3
Order By: Relevance
“…Therefore, if this factor were identified, midwives should aim to provide women with adequate, consistent information about birth in a way which does not trigger anxiety, ensuring sufficient time and emotional support are available in line with World Health Organization guidance . Moreover, Sheen et al suggested that women with FOC have an increased need for informational support since they are more likely to expect a negative outcome from an ambiguous situation due to a characteristic “intolerance of uncertainty” . Findings from a qualitative study in Australia suggest that women with FOC tend to avoid thinking or talking about birth and learning what to expect in labor, and reported that FOC was influenced by the quality of information from professionals .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if this factor were identified, midwives should aim to provide women with adequate, consistent information about birth in a way which does not trigger anxiety, ensuring sufficient time and emotional support are available in line with World Health Organization guidance . Moreover, Sheen et al suggested that women with FOC have an increased need for informational support since they are more likely to expect a negative outcome from an ambiguous situation due to a characteristic “intolerance of uncertainty” . Findings from a qualitative study in Australia suggest that women with FOC tend to avoid thinking or talking about birth and learning what to expect in labor, and reported that FOC was influenced by the quality of information from professionals .…”
Section: Discussionmentioning
confidence: 99%
“…Women were asked to rate their general health from 1 to 5 (poor to very good). Obstetric questions included: gestational age, number of previous children, number of previous miscarriages or stillbirths, any maternal or fetal Isolation"-containing questions relating to perceived social support (comprising four items: 3, 7, 11, 15); and (4) "Moment of Birth"-containing questions relating to how the woman imagines she will feel during birth (comprising three items: 28,29,30). 12 Using a cut-off ≥2.5 (the midpoint) was recommended for comparison purposes.…”
Section: Variablesmentioning
confidence: 99%
“…When measured in the same way, the prevalence of intense fear of childbirth (FOC) varies from 4.8% in Australia to 6.3% in Belgium and 14.8% in Sweden (Nilsson et al, 2018). Women's feelings of uncertainty around the birthing process seem to be a basis for their fear of giving birth (Sheen & Slade, 2018). Fear arising before a woman's first childbirth is labelled primary fear of childbirth, while secondary fear is often related to her earlier birth experiences (Hofberg & Ward, 2003;Lukasse, Schei, & Ryding, 2014;Størksen, Garthus-Niegel, Vangen, & Eberhard-Gran, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Women fearing childbirth can feel a lack of confidence in birth, being influenced by negative birth stories, fear labour pain or losing control, and fear physical injury during birth. Women giving birth again after a previous negative birth experience often fear a repeated poor birth experience (Fenwick et al, 2015;Klabbers et al, 2016;Sheen & Slade, 2018). Fear of childbirth is a multifaceted condition (Dencker et al, 2019) and women with fearing childbirth are a heterogeneous group (Klabbers et al, 2016;Rondung, Ekdahl, Hildingsson, Rubertsson, & Sundin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More fearful women have excessive concerns regarding child malformation, physical damage to the fetus, painful injections, injury to the fetus or themselves during delivery, and fear of pain or of becoming hysterical during delivery [18][19][20]. Understanding what concerns women with serious childbirth fear does not necessarily illuminate why some women are more afraid than others.…”
Section: Introductionmentioning
confidence: 99%